2016
DOI: 10.3389/fncel.2016.00270
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Release of Cytokine IL-3 Triggered by Mechanosensitive Autostimulation of the P2X7 Receptor Is Neuroprotective

Abstract: Mechanical strain due to increased pressure or swelling activates inflammatory responses in many neural systems. As cytokines and chemokine messengers lead to both pro-inflammatory and neuroprotective actions, understanding the signaling patterns triggered by mechanical stress may help improve overall outcomes. While cytokine signaling in neural systems is often associated with glial cells like astrocytes and microglia, the contribution of neurons themselves to the cytokine response is underappreciated and has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 62 publications
2
39
0
Order By: Relevance
“…We hypothesized that the increased expression of following IOP elevation might relate to the release of ATP and autostimulation of P2X7 receptors found in optic nerve head astrocytes exposed to mechanical strain ( Beckel et al, 2014 ). This theory was supported by recent findings implicating the P2X7 receptor in the mechanosensitive upregulation of cytokines IL-3 ( Lim et al, 2016 ) and IL-6 ( Lu et al, 2017 ) in the retina. To determine if the P2X7 receptor was involved in IOP-sensitive priming of IL-1β, the P2X7 receptor antagonist BBG (0.8%) was injected intravitreally 1–3 days before the IOP rise, then retinas were collected 22 h after the IOP returned to baseline.…”
Section: Resultssupporting
confidence: 57%
“…We hypothesized that the increased expression of following IOP elevation might relate to the release of ATP and autostimulation of P2X7 receptors found in optic nerve head astrocytes exposed to mechanical strain ( Beckel et al, 2014 ). This theory was supported by recent findings implicating the P2X7 receptor in the mechanosensitive upregulation of cytokines IL-3 ( Lim et al, 2016 ) and IL-6 ( Lu et al, 2017 ) in the retina. To determine if the P2X7 receptor was involved in IOP-sensitive priming of IL-1β, the P2X7 receptor antagonist BBG (0.8%) was injected intravitreally 1–3 days before the IOP rise, then retinas were collected 22 h after the IOP returned to baseline.…”
Section: Resultssupporting
confidence: 57%
“…), and recent work demonstrates P2X7 receptor stimulation leads to IL‐3 responses in isolated retinal ganglion cells (Lim et al . ). As stimulation of P2X7 receptors by ATP has been associated with the up‐regulation of IL‐6 in microglia cells (Shieh et al .…”
Section: Resultsmentioning
confidence: 97%
“…Stretch did not induce release of lactose dehydrogenase. IL-6 levels were determined with the rat antibody cytokine array following manufacturer's instructions (R & D Systems), as described in detail in a recent publication (Lim et al 2016). In brief, IL-6 levels were quantified by incubating the membrane in Streptavidin-horseradish peroxidase followed by chemiluminescent detection reagents (GE Healthcare).…”
Section: Il-6 Release From Isolated Retinal Ganglion Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microglia activation and proinflammatory signal secretion might induce early mitotic activity in retinal areas adjacent to the optic disc and CMZ (at 55 hpl). It has been demonstrated that cultured RGC from rat samples release cytokines, including TNFα and several interleukins, to the extracellular medium (Lim, Lu, Beckel, & Mitchell, ). Our results showed that TNFα transcriptional expression was increased by 72 hpl, supporting the idea of enhanced TNFα release and its involvement in the induction of multipotent cell proliferation, in addition to its known proinflammatory role.…”
Section: Discussionmentioning
confidence: 99%